A Double‐blind, randomized, placebo‐controlled study to assess the safety, antiviral activity and pharmacokinetics of GSK2336805 when given as monotherapy and in combination with peginterferon alfa‐2a and ribavirin in hepatitis C virus genotype 1‐infected treatment‐naive subjects. (16th October 2013) - Gardner, Stephen; Cutrell, Amy; Elko‐Simms, Cindy; Adkison, Kimberly; Hamatake, Robert; Walker, Jill; Rodriguez‐Torres, Maribel; Hong, Zhi
Abstract Background & Aims GSK2336805 is a HCV NS5A inhibitor for chronic hepatitis C (CHC). In a prior Phase I study, GSK2336805 was well tolerated and had an antiviral and pharmacokinetic profile suitable for once‐daily administration. This 28‐day, double‐blind, randomized, placebo‐controlled study evaluated once daily GSK2336805 60 mg alone or in combination with peginterferon alfa‐2a (180 μg per week) and ribavirin (1000–1200 mg daily) (PEG/RIBA) in treatment‐naive genotype 1 CHC subjects. Methods Five centres enrolled 16 subjects in the USA and Puerto Rico who received GSK2336805 + PEG/RIBA or placebo + PEG/RIBA. Results Following a single monotherapy dose of GSK2336805 on day 1, median reduction from baseline in HCV RNA was −2.96 log10 (N = 11) vs. −0.13 log10 (N = 4) for placebo. With the addition of PEG/RIBA on day 2, subjects receiving GSK2336805 exhibited greater decreases in viral load over the 28‐day treatment period as compared with placebo. At day 28, median reduction from baseline was −4.86 log10 (N = 9) in the GSK2336805 + PEG/RIBA group as compared with −1.98 log10 (N = 4) in the placebo + PEG/RIBA group. At day 28, rapid virological response (RVR) occurred in 8/11 (73%) of the GSK2336805 + PEG/RIBA subjects as compared with 1/4 (25%) of the placebo + PEG/RIBA subjects. Adverse events were consistent with those reported in clinical trials of peginterferon and ribavirin, and no unique adverse events appeared to be associated with GSK2336805. Conclusions GSK2336805 is a potent NS5A inhibitor that showed a substantial antiviral effect as a monotherapy and in combination with peginterferon and ribavirin. ClinicalTrials.gov Identifier: NCT01439373.